2017
DOI: 10.1111/jth.13666
|View full text |Cite
|
Sign up to set email alerts
|

Shear‐sensitive nanocapsule drug release for site‐specific inhibition of occlusive thrombus formation

Abstract: AD, van den Berg A, Murphy AJ, Hagemeyer CE, Peter K, Westein E. Shear-sensitive nanocapsule drug release for site-specific inhibition of occlusive thrombus formation. J Thromb Haemost 2017; 15: 972-82. Essentials• Vessel stenosis due to large thrombus formation increases local shear 1-2 orders of magnitude.• High shear at stenotic sites was exploited to trigger eptifibatide release from nanocapsules.• Local delivery of eptifibatide prevented vessel occlusion without increased tail bleeding times.• Local nanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 31 publications
0
63
0
1
Order By: Relevance
“…Lipid nanocarriers are one such promising mode of nanotechnology that demonstrates substantial potential as a novel drug delivery platform. Preclinical investigations into lipid nanocarriers and their suitability as a drug delivery vehicle in the treatment of thrombosis has been conducted with promising findings, as demonstrated in the study of Molloy et al 17 This group aimed to exploit a key biochemical feature characteristic to thrombosis, being the significantly increased shear stress levels present at the site of thrombus formation. 18 These elevated shear stress levels occur primarily due to the thrombi's restriction of the blood vessel's lumen.…”
Section: Lipid-based Nanocapsules For Treating Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid nanocarriers are one such promising mode of nanotechnology that demonstrates substantial potential as a novel drug delivery platform. Preclinical investigations into lipid nanocarriers and their suitability as a drug delivery vehicle in the treatment of thrombosis has been conducted with promising findings, as demonstrated in the study of Molloy et al 17 This group aimed to exploit a key biochemical feature characteristic to thrombosis, being the significantly increased shear stress levels present at the site of thrombus formation. 18 These elevated shear stress levels occur primarily due to the thrombi's restriction of the blood vessel's lumen.…”
Section: Lipid-based Nanocapsules For Treating Thrombosismentioning
confidence: 99%
“…Hence, the authors reasoned that shear-sensitive nanocapsules could function as a viable means by which to locally deliver antithrombotic drugs to the thrombus. 17 In their study, Molloy et al encapsulated the antiplatelet drug eptifibatide within shear-sensitive phosphatidylcholine (PC)-based (liposomal) nanocapsules, collectively denoted as E-NCs. Using these novel shear-sensitive nanocapsules, they performed an array of in vitro microfluidic flow channel blood perfusion experiments whereby they demonstrated site-specific delivery of eptifibatide to areas of vessel stenosis as well as a shear-dependent release of eptifibatide and inhibition of platelet aggregation.…”
Section: Lipid-based Nanocapsules For Treating Thrombosismentioning
confidence: 99%
“…28 Recently, Molloy et al reported on shear-sensitive phosphatidylcholine-based nanocapsules to achieve site-directed delivery of the antiplatelet drug eptifibatide. 30 When the blood shear stress increased, as resulting from a reduction in the lumen of the vessel, eptifibatide could be released from the system to prevent thrombosis. A polydimethylsiloxane microfluidic stenosis model was also constructed for evaluating platelet function of human blood in stenosis channels.…”
Section: Shear-sensitive Tddsmentioning
confidence: 99%
“…This microfluidic blood perfusion assay showed that the shear-induced eptifibatide nanocapsules inhibited thrombus formation efficiently, particularly at the stenotic section with high shear stress. 30 The second strategy is shear-sensitive nanoparticle aggregates (SS-NPAs) composed of multiple smaller nanoparticles, which are designed to break up in response to high shear rates at site of vascular stenosis. 29,43,44 The micron size SS-NPAs are comparable with platelets, which allow them to aggregate toward the obstructed vessels with high shear.…”
Section: Shear-sensitive Tddsmentioning
confidence: 99%
“…Yet, so far these have been limited to healthy or low WSS conditions and have not addressed VTC adhesion under pathological levels of high WSS where WSS can be 100 dyne/cm 2 and higher . Studies addressing NPs targeting under high WSS region have so far focused on targeting thrombotic arteries and not the endothelium. However, high WSS and endothelial activation are critical aspects known to occur in several disease conditions including vaso‐constricted arteries or at early stages of arteriogenesis following occlusion of a neighboring artery .…”
Section: Introductionmentioning
confidence: 99%